Crystal polymorph of 9,9-bis(6-hydroxy-2-naphthyl)fluorene and its manufacturing method

The novel crystal polymorph δ of BNF, with its higher melting point and specific diffraction peaks, addresses the thermal stability limitations of existing BNF polymorphs, offering enhanced performance in high-temperature environments.

JP7658721B2Active Publication Date: 2025-04-08OSAKA GAS CHEM KK
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2020057496
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-03-28
Filing Date
2020-03-27
Publication Date
2025-04-08
Estimated Expiration
2040-03-27

AI Technical Summary

Technical Problem

The existing crystal polymorphs of 9,9-bis(6-hydroxy-2-naphthyl)fluorene (BNF) have relatively high melting points but may not provide sufficient thermal stability in high-temperature environments, limiting their usage.

Method used

A novel crystal polymorph δ of BNF is developed, characterized by specific diffraction peaks in the powder X-ray diffraction pattern and a significantly higher melting point of 264±3°C, achieved through crystallization from a mixed solvent of aromatic hydrocarbons and phenols, ketones, or ethers.

Benefits of technology

The crystal polymorph δ exhibits excellent thermal stability and storage stability under high-temperature conditions, making it suitable for a wide range of applications, including industrial products, resin raw materials, and additives.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007658721000004
    Figure 0007658721000004
  • Figure 0007658721000005
    Figure 0007658721000005
  • Figure 0007658721000006
    Figure 0007658721000006
Patent Text Reader

Abstract

To provide a novel polymorph of BNF (crystal polymorph) that has an excellent heat stability or storage stability in a high temperature environment, and to provide a method for producing the same.SOLUTION: By crystallizing BNF from a mixed solvent of aromatic hydrocarbons and at least one solvent selected from phenols and ketones, a crystalline polymorph δ having diffraction peaks at diffraction angles 2θ=9.6±0.2°, 20.6±0.2° and 21.3±0.2° in powder X-ray diffraction pattern is obtained. The crystalline polymorph δ may also have diffraction peaks at at least one angle selected from diffraction angles 2θ=9.2±0.2°, 9.8±0.2°, 17.1±0.2°, 23.3±0.2° and 23.8±0.2°.SELECTED DRAWING: Figure 7
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a novel polymorph (or crystalline polymorph) of 9,9-bis(6-hydroxy-2-naphthyl)fluorene. [Background technology]

[0002] Compounds having a 9,9-bisarylfluorene skeleton have excellent optical properties such as a high refractive index and thermal properties such as heat resistance, and are effectively used as resin raw materials and additives.

[0003] For example, Patent Document 1 discloses 6,6-(9-fluorenylidene)-di(2-naphthol) [or 9,9-bis(6-hydroxy-2-naphthyl)fluorene: hereinafter also referred to as BNF] as a compound having a 9,9-bisarylfluorene skeleton, and describes that the BNF has three crystalline polymorphs produced by a specified method, namely, crystalline polymorph α (hereinafter also referred to as α crystal), crystalline polymorph β (hereinafter also referred to as β crystal), and crystalline polymorph γ (hereinafter also referred to as γ crystal). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2012-207008 A Summary of the Invention [Problem to be solved by the invention]

[0005] It is described that the α-, β- and γ-crystals of BNF obtained by the method described in Patent Document 1 have relatively high heat resistance due to the 9,9-bisarylfluorene skeleton, and the melting points of each crystal are approximately 213°C, 226°C and 230°C, respectively.

[0006] However, depending on the usage environment or storage conditions, the thermal stability may be insufficient, which may limit the applications of the material, and therefore there is a demand for even higher thermal stability or storage stability under high temperature environments.

[0007] Therefore, an object of the present invention is to provide a novel polymorph (crystalline polymorph) of BNF having excellent thermal stability or storage stability in a high-temperature environment, and a method for producing the same. [Means for solving the problem]

[0008] As a result of intensive research to achieve the above object, the present inventors have found that when BNF is crystallized from a specific crystallization solvent, a novel crystalline polymorph δ (hereinafter also referred to as δ crystal) having an extremely high melting point, unlike the α crystal, β crystal, and γ crystal described in Patent Document 1, can be obtained, and have completed the present invention.

[0009] That is, the crystalline polymorph δ of the present invention is a crystalline polymorph of 9,9-bis(6-hydroxy-2-naphthyl)fluorene (BNF), and has diffraction peaks at diffraction angles 2θ=9.6±0.2°, 20.6±0.2°, and 21.3±0.2° in a powder X-ray diffraction pattern.

[0010] The crystalline polymorph δ may further have a diffraction peak at at least one angle selected from the diffraction angles 2θ=9.2±0.2°, 9.8±0.2°, 17.1±0.2°, 23.3±0.2°, and 23.8±0.2°. The crystalline polymorph δ may further have a diffraction peak at at least one angle selected from the diffraction angles 2θ=13.3±0.2°, 14.5±0.2°, 15.5±0.2°, and 26.8±0.2°. The crystalline polymorph δ may have the largest peak intensity at a diffraction angle 2θ=19.5±0.2°. The crystalline polymorph δ may have a melting point of 264±3°C.

[0011] The present invention also includes a method for producing the crystalline polymorph δ by crystallizing 9,9-bis(6-hydroxy-2-naphthyl)fluorene from a mixed solvent of aromatic hydrocarbons and at least one solvent selected from phenols, ketones, and ethers. In the method, the ratio of the aromatic hydrocarbons to the total amount of phenols, ketones, and ethers may be about 70 / 30 to 90 / 10 (mass ratio). In the method, the precipitation (or crystallization) may be performed at -10°C to 10°C.

[0012] The crystalline polymorph δ of the present invention may be the following polymorph. That is, it may be a crystalline polymorph of 9,9-bis(6-hydroxy-2-naphthyl)fluorene (BNF), and may have diffraction peaks at diffraction angles 2θ=9.6±0.2° and 21.3±0.2° in a powder X-ray diffraction pattern. The crystalline polymorph δ may further have a diffraction peak at at least one angle selected from diffraction angles 2θ=9.2±0.2°, 9.8±0.2°, 17.1±0.2°, 23.3±0.2° and 23.8±0.2°. The crystalline polymorph δ may further have a diffraction peak at at least one angle selected from diffraction angles 2θ=14.2±0.2°, 16.7±0.2°, 19.1±0.2°, 19.5±0.2° and 20.6±0.2°. The crystalline polymorph δ may have the largest peak intensity at a diffraction angle 2θ=19.5±0.2°. The crystalline polymorph δ may have a melting point of 264±3° C. Furthermore, the present invention also encompasses a method for producing the crystalline polymorph δ by crystallizing 9,9-bis(6-hydroxy-2-naphthyl)fluorene from a mixed solvent of aromatic hydrocarbons and at least one solvent selected from phenols and ketones.

[0013] In this specification and claims, the number of carbon atoms is represented as C1, C6, C 10 For example, an alkyl group with one carbon atom is represented as "C1 alkyl" and an aryl group with 6 to 10 carbon atoms is represented as "C 6-10 It is indicated as "aryl". Effect of the Invention

[0014] The crystalline polymorph δ of BNF of the present invention has an extremely high melting point and is therefore excellent in thermal stability or storage stability in high temperature environments, and can therefore be used in a wide range of applications, such as industrial products, organic compounds, resin raw materials, and resin additives. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 is a chart showing the powder X-ray diffraction pattern of BNF prepared as a raw material for obtaining the crystalline polymorph δ in Example 1. [Diagram 2] FIG. 2 is a chart showing the powder X-ray diffraction pattern of the crystalline polymorph δ obtained in Example 1. [Diagram 3] FIG. 3 is a DSC chart of the crystalline polymorph δ obtained in Example 1, in which the solid line indicates DSC and the dashed line indicates DDSC. [Figure 4] FIG. 4 is a chart showing the powder X-ray diffraction pattern of the crystalline polymorph α obtained in Comparative Example 1. [Diagram 5] FIG. 5 is a chart showing the powder X-ray diffraction pattern of the crystalline polymorph β obtained in Comparative Example 2. [Figure 6] FIG. 6 is a chart showing the powder X-ray diffraction pattern of the crystalline polymorph γ obtained in Comparative Example 3. [Figure 7] FIG. 7 is a chart showing the powder X-ray diffraction pattern of the crystalline polymorph δ obtained in Example 4. [Figure 8] FIG. 8 is a chart showing the powder X-ray diffraction pattern of the crystalline polymorph δ obtained in Example 6. [Figure 9] FIG. 9 is a DSC chart of the crystalline polymorph δ obtained in Example 3, in which the solid line indicates DSC and the dashed line indicates DDSC. [Figure 10] FIG. 10 is a DSC chart of the crystalline polymorph δ obtained in Example 4, in which the solid line indicates DSC and the dashed line indicates DDSC. [Figure 11] FIG. 11 is a DSC chart of the crystalline polymorph δ obtained in Example 5, in which the solid line indicates DSC and the dashed line indicates DDSC. [Figure 12] FIG. 12 is a DSC chart of the crystalline polymorph δ obtained in Example 6, in which the solid line indicates DSC and the dashed line indicates DDSC. [Figure 13] FIG. 13 is a DSC chart of the crystalline polymorph δ obtained in Example 7, in which the solid line indicates DSC and the dashed line indicates DDSC. [Figure 14] FIG. 14 is a DSC chart of the mixture of crystalline polymorphs α and δ obtained in Example 8, in which the solid line indicates DSC and the dashed line indicates DDSC. [Figure 15] FIG. 15 is a chart showing the powder X-ray diffraction pattern of the amorphous body obtained in Reference Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] [Characteristics of polymorph δ] The crystalline polymorph δ of the present invention is a crystalline polymorph of 9,9-bis(6-hydroxy-2-naphthyl)fluorene (BNF), and has at least characteristic diffraction peaks at diffraction angles 2θ=9.6±0.2°, 20.6±0.2°, and 21.3±0.2° in a powder X-ray diffraction pattern (XRD). Preferably, it also has characteristic diffraction peaks at at least one angle selected from the diffraction angles 2θ=9.2±0.2°, 9.8±0.2°, 17.1±0.2°, 23.3±0.2°, and 23.8±0.2°, more preferably at least two angles, at least three angles, at least four angles, and even more preferably all five angles selected in the following order of steps.

[0017] Usually, the crystalline polymorph δ further has a diffraction peak at at least one angle selected from the diffraction angles 2θ=13.3±0.2°, 14.5±0.2°, 15.5±0.2°, and 26.8±0.2°. Of these diffraction angles 2θ, preferably, the diffraction peak is at at least one angle selected from the diffraction angles 2θ=14.5±0.2°, 15.5±0.2°, and 26.8±0.2°, more preferably, at least the diffraction angle 2θ=14.5±0.2°.

[0018] The crystalline polymorph δ may further have a diffraction peak at at least one angle selected from the diffraction angles 2θ=12.4±0.2°, 13.9±0.2°, 14.2±0.2°, 15.1±0.2°, 17.5±0.2°, 18.6±0.2°, 19.1±0.2°, 19.5±0.2°, 24.7±0.2°, 26.4±0.2°, and 29.5±0.2°. Of these diffraction angles 2θ, the diffraction peak is preferably at at least one angle selected from the diffraction angles 2θ=13.9±0.2°, 15.1±0.2°, 17.5±0.2°, and 24.7±0.2°, and more preferably at at least one angle selected from the diffraction angles 2θ=17.5±0.2° and 24.7±0.2°.

[0019] The crystal polymorph δ may have the diffraction peak pattern as described above, and the largest peak intensity I (integral intensity I s and / or peak height I h ) may or may not have a diffraction peak at an angle selected from 17.5±0.2°, 20.6±0.2°, 21.3±0.2°, and 24.7±0.2°, and the intensity I (integrated intensity I s and / or peak height I h ) is the largest, and among them, the intensity I6 of the diffraction peak at 20.6±0.2° (integrated intensity I 6s and / or peak height I 6h The integrated intensities at the peaks at diffraction angles 2θ=17.5±0.2°, 20.6±0.2°, 21.3±0.2°, and 24.7±0.2° are respectively represented by I 5s , I 6s , I 7s and I 10s Then, the order (or relationship) of the integral intensities is usually I 6s ≧I 5s ,I 7s ,I 10s (i.e., I 6s But, I 5s , I 7s and I 10s It is preferable that the above is the case.

[0020] In the present specification and claims, the order of peak intensities, for example, "I 6s ≧I 5s ,I 7s ,I 10s " is I 6s I 5s , I 7s and I 10s This means that the order between the peak intensities described with "," is equal to or greater than the above, i.e., I in the above example 5s ,I 7s ,I 10s The order between them is not particularly limited.

[0021] On the other hand, the integrated intensities of the diffraction peaks at diffraction angles 2θ = 9.6 ± 0.2°, 21.3 ± 0.2°, 9.2 ± 0.2°, 9.8 ± 0.2°, 23.3 ± 0.2°, and 23.8 ± 0.2° are, respectively, 2s , I 7s , I 1s , I 3s , I 8s and I 9s Then, the order (or relationship) of the integral intensities is usually I 2s ,I 7s ≧I 1s ,I 3s ,I 8s ,I 9s and preferably I 7s ≧I 2s ≧I 1s ,I 3s ,I 8s ,I 9s It is.

[0022] Also preferably I 6s ≧I 2s ,I 7s The order is as follows.

[0023] Polymorph δ usually has at least a diffraction peak at a diffraction angle 2θ=20.6±0.2° and the diffraction peaks shown in Table 1 below. Furthermore, in polymorph δ, the integrated intensity I 6s and peak height I6h When the integral intensity and peak height are set to "100", the integral intensity and peak height can be shown in Table 1 below, and the powder X-ray diffraction pattern is preferably as shown in FIG.

[0024] [Table 1]

[0025] The above powder X-ray diffraction pattern can be measured using a conventional powder X-ray diffractometer. Note that the diffraction angle 2θ at which the peak appears may vary by about ±0.2° or ±0.1° depending on the measurement conditions.

[0026] The α crystals obtained by the method of Patent Document 1 exhibit characteristic peaks at diffraction angles 2θ=12.4±0.2°, 14.3±0.2°, 16.8±0.2°, 19.2±0.2°, 19.6±0.2°, and 22.1±0.2° in the powder X-ray diffraction pattern as shown in Figure 4. The peak at a diffraction angle 2θ=19.6±0.2° is often the largest. Although the diffraction pattern of α crystals has some similarities to the pattern of δ crystals, it does not have the characteristic peaks of δ crystals, i.e., diffraction peaks at diffraction angles 2θ=9.6±0.2°, 20.6±0.2°, and 21.3±0.2°, and preferably does not have diffraction peaks at diffraction angles 2θ=9.2±0.2°, 9.8±0.2°, 17.1±0.2°, 23.3±0.2°, and 23.8±0.2°, and is therefore different from the diffraction pattern of δ crystals.

[0027] In addition, the β crystal obtained by the method of Patent Document 1 shows characteristic peaks at diffraction angles 2θ=11.9±0.2°, 14.1±0.2°, 17.8±0.2°, 18.5±0.2°, 19.9±0.2°, 22.1±0.2°, and 22.9±0.2° in the powder X-ray diffraction pattern, as shown in FIG. 5. Among these peaks, the peak at the diffraction angle 2θ=17.8±0.2° or 22.9±0.2° is often large. Such a powder X-ray diffraction pattern is significantly different from the diffraction pattern of the δ crystal.

[0028] The γ crystals obtained by the method of Patent Document 1 show characteristic peaks at diffraction angles 2θ=6.0±0.2°, 17.4±0.2°, 17.9±0.2°, 18.5±0.2°, 21.1±0.2°, 21.8±0.2°, 22.7±0.2°, and 23.6±0.2° in the powder X-ray diffraction pattern as shown in Figure 6. Such a powder X-ray diffraction pattern is also significantly different from the diffraction pattern of the δ crystals.

[0029] The crystalline polymorph δ of BNF of the present invention has a significantly higher melting point than the crystalline polymorphs α, β, and γ described in Patent Document 1, and is, for example, 264±5°C, preferably 264±3°C, and more preferably 264±2°C, when measured by differential scanning calorimetry (DSC). Therefore, the crystalline polymorph δ is excellent in thermal stability (or heat resistance) or storage stability in a high-temperature environment. The melting point can be measured based on the peak top of the endothermic peak (or melting point) in differential scanning calorimetry (DSC).

[0030] [Method of producing crystalline polymorph δ] The crystalline polymorph δ can be prepared by crystallizing 9,9-bis(6-hydroxy-2-naphthyl)fluorene (BNF) from a mixed solvent of aromatic hydrocarbons and at least one solvent selected from phenols, ketones, and ethers. A preferred crystallization solvent is a mixed solvent of aromatic hydrocarbons, phenols, and ketones.

[0031] Examples of the aromatic hydrocarbons include benzene and alkylbenzenes. Examples of alkylbenzenes include mono- to tetra-C alkylbenzenes such as xylene, ethylbenzene, trimethylbenzene, ethyltoluene, propylbenzene, and cumene. 1-4 Alkyl-benzenes and the like.

[0032] These aromatic hydrocarbons may be used alone or in combination of two or more. Among these aromatic hydrocarbons, mono- to tri-C 1-3 Alkyl-benzenes are preferred, more preferably diC 1-2An alkyl-benzene is preferred, and xylene is more preferred. From the viewpoint of excellent solubility, o-xylene or m-xylene is preferred, and o-xylene is most preferred.

[0033] Examples of the phenols include C phenols such as phenol, cresol, xylenol, naphthol, and methylnaphthol. 6-12 Phenol, etc.

[0034] These phenols may be used alone or in combination of two or more. 6-10 Phenol is preferred, naphthols such as 1-naphthol and 2-naphthol are more preferred, and 2-naphthol is particularly preferred because of its excellent solubility.

[0035] The ketones are usually chain ketones, such as C ketones such as acetone, methyl ethyl ketone (MEK), methyl propyl ketone, methyl isopropyl ketone, diethyl ketone, methyl isobutyl ketone (MIBK), diisopropyl ketone, and butyl propyl ketone. 3-8 Ketones, etc.

[0036] These ketones may be used alone or in combination of two or more. 4-7 Ketones are preferred, and from the viewpoint of solubility, C 5-7 Ketones are more preferred.

[0037] Examples of ethers include C ethers such as diethyl ether and diisopropyl ether. 1-6 Chain ethers; C such as tetrahydrofuran, tetrahydropyran, and 1,4-dioxane 3-6 Examples include cyclic ethers.

[0038] These ethers may be used alone or in combination of two or more. Among these ethers, cyclic ethers are preferred, and from the viewpoint of solubility, C ethers such as 1,4-dioxane are preferred. 3-5 Cyclic ethers are more preferred.

[0039] The typical crystallization solvent is mono- or di-C 1-2 Alkyl-benzene and C 6-12 Phenol, C 4-7 Ketones, and C 3-6 and the like. Examples of the solvent include a mixed solvent of at least one solvent selected from the group consisting of cyclic ethers, and the like. Preferred are xylene such as o-xylene and naphthol such as 2-naphthol, and C 5-7 Ketones, and 1,4-dioxane, etc. 3-5 A mixed solvent containing at least one solvent selected from the group consisting of cyclic ethers, more preferably a mixed solvent containing xylene such as o-xylene, naphthol such as 2-naphthol, and C 5-7 or a mixture of xylene, such as o-xylene, and C 5-7 It is a mixed solvent of ketones, especially xylene such as o-xylene and C 5-7 It is a mixed solvent with ketone.

[0040] In the crystallization solvent, aromatic hydrocarbons such as xylene, phenols such as naphthol, C 5-7The mass ratio of the total amount of ketones such as ketones and ethers such as cyclic ethers may be, for example, about 1 / 99 to 99 / 1, and the preferred range may be 10 / 90 to 97 / 3, 30 / 70 to 95 / 5, 50 / 50 to 95 / 5, 60 / 40 to 90 / 10, 65 / 35 to 85 / 15, 70 / 30 to 80 / 20, 75 / 25 to 80 / 20, and 70 / 30 to 90 / 10, preferably 75 / 25 to 88 / 12, and more preferably 80 / 20 to 85 / 15, in particular, from the viewpoint that δ crystals can be efficiently formed by precipitating at a lower temperature. If the total amount of phenols, ketones and ethers, which are good solvents for BNF, is too small, δ crystals may not be formed, and if it is too large, crystals may not be efficiently precipitated.

[0041] The crystallization solvent is phenols such as naphthol and C 5-7 In the case where both phenols and ketones such as ketones are contained, the mass ratio of the phenols to the ketones may be, for example, the former / the latter=about 1 / 99 to 99 / 1, and preferred ranges are as follows, in the following stepwise order: 5 / 95 to 90 / 10, 10 / 90 to 70 / 30, 15 / 85 to 60 / 40, 20 / 80 to 50 / 50, 25 / 75 to 45 / 55, and 30 / 70 to 40 / 60.

[0042] The crystallization solvent may contain other solvents different from the aromatic hydrocarbons, phenols, and ketones. The other solvents may be conventional organic solvents or water. The water may be in the form of an aqueous solution, and representative aqueous solutions include aqueous solutions of inorganic acids such as hydrochloric acid and sulfuric acid, and the concentration of the aqueous solution may be, for example, about 0.1 to 10% by mass. The proportion may be, for example, 30% by mass or less, usually about 0 to 20% by mass, with the preferred range being 10% by mass or less, 5% by mass or less, 1% by mass or less, 0.1% by mass or less, and more preferably 0% by mass, i.e., substantially no other solvents.

[0043] The proportion (or amount used) of the crystallization solvent is not particularly limited and may be, for example, about 0.1 to 20 parts by mass relative to 1 part by mass of the fluorene compound BNF (solid content equivalent), and preferred ranges are 0.5 to 15 parts by mass, 1 to 10 parts by mass, 2 to 7 parts by mass, 3 to 5 parts by mass, and 3.5 to 4.5 parts by mass in the following stepwise order.

[0044] The crystalline polymorph δ can be precipitated by dissolving BNF in the crystallization solvent and cooling. Usually, the crystalline polymorph δ can be precipitated or crystallized by dissolving BNF in the crystallization solvent by heating and cooling. After dissolving, if necessary, a predetermined amount of the solvent may be distilled off under reduced pressure to adjust the amount of the crystallization solvent to the range of the ratio. In addition, the crystallization solvent may be added (or mixed) in advance in all the solvents before heating, or may be added stepwise, for example, a portion of the solvent may be added, the temperature may be raised to a predetermined temperature, and then the remaining solvent may be added.

[0045] In addition, BNF may be prepared by the method described in Patent Document 1, for example, by a conventional method such as a method of reacting 9-fluorenone with 2-naphthol (or β-naphthol) in the presence of an acid catalyst such as sulfuric acid and a cocatalyst such as β-mercaptopropionic acid. In addition, BNF may be crystallized by dissolving an isolated fluorene compound in the crystallization solvent, regardless of whether it is in a crystalline form such as the crystal polymorphs α, β, or γ prepared by the method described in Patent Document 1 or in an amorphous form, and in the synthesis reaction of BNF, after the reaction is completed, the solvent of the reaction mixture may be replaced with the crystallization solvent to crystallize the crystal polymorph δ. For example, the reaction mixture may be neutralized and washed as necessary, and then the solvent or dispersion medium may be removed from the reaction mixture, and the residue may be dissolved in the crystallization solvent to crystallize the crystal polymorph δ.

[0046] The temperature at which the BNF is dissolved in the crystallization solvent is a temperature below the boiling point of the solvent, for example, 30 to 200°C, and preferred ranges are 50 to 150°C, 60 to 130°C, 70 to 120°C, and 80 to 110°C in the following stepwise order.

[0047] The obtained BNF solution is cooled to crystallize the crystalline polymorph δ. The crystallization may be performed by quenching, cooling or slow cooling, and crystalline polymorph δ appears to be relatively easy to obtain by quenching. A typical cooling rate can be selected from the range of about 0.1 to 100°C / min, for example, and the preferred ranges are 1°C / min or more, 1 to 50°C / min, 3 to 30°C / min, 5 to 20°C / min, 7 to 15°C / min, 8 to 12°C / min, and 9 to 11°C / min, in the following stepwise manner. In addition, the lower the precipitation temperature (the temperature at which precipitation or crystallization begins), the easier it is to obtain the crystalline polymorph δ, and the range may be selected from the range of about 80°C or less, for example, and the preferred ranges are 70°C or less, 50°C or less, 30°C or less, 20°C or less, -10°C to 20°C, -5°C to 15°C, and particularly 10°C or less, and 0 to 10°C is preferred. The ultimate cooling temperature is, for example, −10° C. to 30° C., preferably −5° C. to 20° C., and more preferably 0 to 10° C. The retention time at the ultimate cooling temperature is not particularly limited and may be, for example, about 1 minute to 12 hours, preferably 0.5 to 6 hours, and more preferably 1 to 3 hours.

[0048] In the crystallization procedure, seed crystals may be added if necessary, and the crystallization procedure may be performed once or repeatedly. The crystals produced by the crystallization are usually filtered by a separation means such as filtration by suction filtration or centrifugation, and then dried to obtain the crystalline polymorph δ having a high melting point.

[0049] The drying may be performed under reduced pressure, and the drying temperature may be, for example, about 50 to 200° C., and the preferred ranges are 80 to 160° C., 90 to 150° C., 100 to 140° C., and 110 to 130° C. in the following stepwise manner. The temperature may be raised all at once for drying, but is usually raised in steps for drying. The drying time may be, for example, about 1 hour to 1 week, and is preferably 1 to 3 days. EXAMPLES

[0050] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. Each evaluation method is as follows.

[0051] [Evaluation method] (X-ray diffraction (XRD)) The measurements were performed using a powder X-ray diffractometer (Rigaku Corporation, "Fully automated multipurpose horizontal X-ray diffractometer Smart Lab") at an output of 3 kW, a radiation source (Cu tube), and a measurement angle of 5 to 70° or 5 to 90°.

[0052] (Melting Point) A differential scanning calorimeter (SII NanoTechnology, Inc., "EXSTAR DSC6200") was used to measure under conditions of a nitrogen atmosphere, a measurement temperature of 30 to 300°C, and a heating rate of 10°C / min. From the obtained DSC chart (DSC curve), the temperature at the top of the endothermic peak due to melting was calculated as the melting point.

[0053] [Example 1] (Preparation of BNF) 28.8g of 99% 9-fluorenone, 69.2g of β-naphthol, 0.43ml of β-mercaptopropionic acid, 40.0g of 1,4-dioxane, and 22.4ml of 98% sulfuric acid were added to a 1L glass vessel equipped with a stirrer, a cooler, and a thermometer, and the reaction was carried out by stirring at 60°C for 6 hours. As a result of confirmation by HPLC, the remaining amount of fluorenone was 0.1% or less. After adding 13.3g of 1,4-dioxane, 200g of o-xylene, and 53.3g of water to the obtained reaction liquid, 53.3g of 5% sodium bicarbonate water (sodium bicarbonate aqueous solution) was added to neutralize the solution until the pH became 7, and the water layer was removed. The obtained organic layer was heated to 80°C, and then washed three times with 80g of water. The washed organic layer was concentrated under reduced pressure to obtain 9,9-bis(6-hydroxy-2-naphthyl)fluorene (BNF). In addition, 1 The obtained compound was confirmed to be the desired BNF by 1 H-NMR.

[0054] The powder X-ray diffraction pattern of the obtained BNF (raw material for the δ crystal) is shown in FIG.

[0055] X-ray diffraction peaks (relative integrated intensity; relative peak height in parentheses): diffraction angle 2θ = 8.22° (43.01; 38.57), 10.99° (53.61; 49.35), 11.97° (31.81; 38.5), 12.33° (28.17; 40.99), 12.59° (38.15; 39.84), 13.45° (14.78; 20.68), 13.72° (46.13; 34.48), 14.25° (15.39; 26.58), 14.51° (1.2; 5.15), 15.50°(25.18;34.76), 16.22°(34.33;48.35), 16.66°(89.56;88.09), 17.38°(27.98;22.08), 17.72°(74.81;90.45), 19.13°(77.59;65.6), 19.53°(37.68;68.31), 20.52°(88.03;86.5), 21.53°(54.37;23.92), 21.97°(100;100), 22.78°(20.41;14.85), 2 3.08°(40.07;41.07), 25.00°(17.31;24.85), 25.35°(18.49;24.29), 25.95°(13.94;21.02), 26.36°(10.43;12.3), 26.82°(63.93;67.12), 27.41°(34.45;38.52), 27.74°(8.75;13.36), 28.17°(5.14;7.38), 29.04°(6.52;8.83), 29.58°(3.63;8.75), 30. 48°(15.37;12.51), 31.90°(1.57;3.7), 33.58°(2.79;2.87), 37.83°(4.75;5.21), 39.61°(0.98;2.13), 40.62°(4.19;3.94), 43.44°(13.91;7.47), 44.86°(4.15;2.74), 46.54°(3.09;0.84), 53.16°(2.74;1.97), 56.82°(1.44;0.46), 58.97°(1.06;0.36).

[0056] The obtained BNF is presumed to be a mixture (or a mixture) of α and β crystals.

[0057] (Preparation of BNF polymorph δ) 5g of BNF was mixed with 15g of o-xylene and 1.5g of 2-naphthol, and heated to 100°C. Then, 3g of methyl isobutyl ketone (MIBK) was added and dissolved. Then, the mixture was cooled at 10°C / min and cooled with ice for 2 hours at 10°C or less (after reaching 10°C by cooling, the mixture was kept in the temperature range of 0 to 10°C for 2 hours with ice) to precipitate crystals. The crystals collected by suction filtration were washed with o-xylene, dried under reduced pressure at 90°C for 1 day, and further dried under reduced pressure at 120°C for 1 day to obtain the crystalline polymorph δ (δ crystals) of BNF.

[0058] The powder X-ray diffraction pattern of the obtained δ crystal is shown in FIG.

[0059] X-ray diffraction peaks (relative integrated intensity; relative peak height in parentheses): diffraction angles 2θ = 9.23° (23.1; 21.3), 9.60° (50.2; 40.5), 9.82° (32.4; 26.4), 12.35° (46.3; 41.5), 13.25° (27.2; 18.1), 13.91° (38.6; 34.4), 14.17° (66.2; 57.1), 14.52° (58.5; 40.6), 15.13° (31.1; 23.5), 15.51° (37.5; 43.6), 17.13° (32 .7;34.4), 17.54°(59.3;56.3), 18.56°(21.1;25.1), 19.07°(86.7;64.6), 19.53°(124.8;112.8), 20.63°(100;100), 21.28°(55.5;46.2), 23.31°(29.2;26.4), 23.75°(20.8;15.3), 24.69°(55.4;37.0), 26.35°(49.4;34.9), 26.77°(38.4;34.5), 29.51°(37.2;25.5).

[0060] The melting point of the obtained δ crystals was 264.4° C. The DSC chart of the obtained δ crystals is shown in FIG.

[0061] [Example 2] δ crystals of BNF were obtained in the same manner as in Example 1, except that 197 g of o-xylene, 20 g of 2-naphthol, and 39 g of MIBK were added to 66 g of BNF and dissolved by heating to 88°C. The powder X-ray diffraction pattern of the obtained δ crystals was similar to the diffraction pattern of the δ crystals obtained in Example 1 (Figure 2). It was found that δ crystals could be obtained even if MIBK was added before heating. The melting point was 263.9°C.

[0062] [Comparative Example 1] α-crystal described in Patent Document 1 The crystalline polymorph α (α crystal) of BNF was obtained according to Example 1 of Patent Document 1. The crystals (α crystal) started to precipitate when toluene was added after o-xylene was removed from the organic layer, so the crystal precipitation temperature was 60° C. or higher. The powder X-ray diffraction pattern of the obtained α crystal is shown in FIG.

[0063] X-ray diffraction peaks (relative peak heights are shown in parentheses): diffraction angles 2θ = 7.12° (18.86), 8.22° (34.91), 10.90° (20.75), 12.40° (43.55), 14.30° (52.32), 16.78° (86.54), 19.18° (65.79), 19.64° (100.00), 22.12° (56.71), 22.82° (41.05), 22.90° (41.05), 25.08° (36.10), 26.50° (32.02), 27.82° (21.93), 29.62° (23.38), 32.02° (16.93).

[0064] The melting point of the obtained α crystals was 213°C.

[0065] [Comparative Example 2] β crystal described in Patent Document 1 A crystalline polymorph β (β crystal) of BNF was obtained according to Example 3 of Patent Document 1. The powder X-ray diffraction pattern of the obtained β crystal is shown in FIG.

[0066] X-ray diffraction peaks (relative peak heights are shown in parentheses): diffraction angles 2θ = 5.88° (30.96), 10.86° (41.56), 11.92° (59.38), 11.94° (59.38), 14.06° (68.76), 17.84° (88.74), 18.48° (80.96), 19.92° (86.59), 21.88° (65.95), 22.06° (61.91), 22.92° (100.00), 27.90° (46.53).

[0067] The melting point of the resulting β crystals was 226°C.

[0068] [Comparative Example 3] γ crystals described in Patent Document 1 A crystalline polymorph γ (γ crystal) of BNF was obtained according to Reference Example 1 of Patent Document 1. The powder X-ray diffraction pattern of the obtained γ crystal is shown in FIG.

[0069] X-ray diffraction peaks (relative integrated intensity; relative peak heights are shown in parentheses): diffraction angles 2θ = 6.00° (100.00), 12.16° (29.78), 15.12° (37.04), 16.50° (44.21), 17.40° (69.14), 17.92° (53.47), 18.46° (53.47), 18.50° (53.47), 19.14° (46.30), 21.08° (56.79), 21.84° (59.88), 22.68° (52.16), 23.62° (53.47), 24.74° (40.59), 27.36° (35.96).

[0070] The melting point of the obtained γ crystals was 230°C.

[0071] The properties of the polymorphs obtained in Example 1 and Comparative Examples 1 to 3 are shown in Table 2.

[0072] [Table 2]

[0073] As is clear from Table 2, it was found that the δ crystal obtained in Example 1 exhibited a melting point that was about 30 to 50° C. higher than that of the comparative example.

[0074] [Examples 3 to 7] Each component shown in Table 3 was added to a vial, mixed, and heated to the dissolution temperature shown in Table 3 to dissolve. As for BNF, BNF (a mixture of α crystals and β crystals) prepared in the same manner as in Example 1 (Preparation of BNF) was used. Thereafter, the obtained solution was cooled at 10°C / min, and ice-cooled at 10°C or less for 2 hours (after reaching 10°C by cooling, it was kept in the temperature range of 0 to 10°C for 2 hours with ice) to precipitate crystals. The crystals collected by suction filtration were washed with o-xylene, dried under reduced pressure at 90°C for 1 day, and then further dried under reduced pressure at 120°C for 1 day to obtain crystals of BNF.

[0075] The powder X-ray diffraction patterns of the crystals obtained in Example 4 and Example 6 are shown in Figure 7 and Figure 8, respectively, and the main diffraction peaks are shown below. The melting points of the crystals are shown in Table 3, and the DSC charts are shown in Figures 9 to 13.

[0076] X-ray diffraction peaks of the crystals obtained in Example 4 (relative integrated intensity; relative peak height are shown in parentheses): diffraction angle 2θ = 9.25° (25.4; 17.6), 9.59° (40.9; 35.6), 9.82° (18.7; 20.5), 12.32° (8.0; 7.0), 13.27° (20.0; 18.3), 13.95° (34.0; 31.5), 14.17° (13.8; 22.1), 14.60° (32.4; 20.6), 15.12° (25.5; 22.2), 15.52° (28.1; 33.9), 17.1 3°(55.4;41.1), 17.53°(49.0;56.7), 18.54°(14.0;16.9), 18.89°(10.5;10.9), 19.52°(8.7;8.1), 20.62°(100.0;100.0), 21.26°(64.9;51.9), 23.23°(25.2;24.4), 23.77°(21.7;21.8), 24.54°(69.1;42.9), 26.35°(25.0;16.9), 26.80°(31.9;29.8), 29.48°(15.4;10.2).

[0077] X-ray diffraction peaks of the crystals obtained in Example 6 (relative integrated intensity; relative peak height are shown in parentheses): diffraction angle 2θ = 9.20° (22.7; 14.9), 9.54° (37.3; 29.9), 9.78° (21.7; 20.3), 12.50° (10.3; 7.3), 13.26° (36.8; 24.6), 13.87° (39.4; 30.6), 14.10° (29.8; 29.9), 14.53° (39.1; 30.4), 15.07° (33.4; 29.8), 15.46° (46.2; 43.6), 17.07° (33.4; 29.8 ... .15°(41.6;41.2), 17.49°(74.1;69.0), 18.51°(19.7;21.4), 18.87°(8.8;9.1), 19.76°(7.8;3.8), 20.58°(100.0;100.0), 21.22°(71.8;53.9), 23.15°(36.2;26.1), 23.71°(14.7;18.8), 24.52°(62.4;40.3), 26.31°(19.6;15.1), 26.72°(27.5;29.5), 29.34°(12.7;9.6).

[0078] [Example 8] 90g of BNF (mixture of α crystals and β crystals) prepared in the same manner as in Example 1 (preparation of BNF), 260g of o-xylene, 75g of 1,4-dioxane, and 33g of 2-naphthol were added to a 1L eggplant flask and dissolved at 80°C, and 245g of the solvent was removed by distillation using an evaporator. The evaporator was operated under conditions of 70°C, 40-60 Torr, and 30 minutes. 260g of o-xylene heated to 70°C was added to the residual liquid to confirm that no precipitation occurred. The mixture was stirred while kept at 70°C, and when rapid precipitation of crystals was confirmed, it was kept at 70°C for 30 minutes. The precipitated crystals were suction filtered, washed with o-xylene, and dried under reduced pressure at 80°C for 2 days to obtain crystals of BNF.

[0079] The melting point of the crystals obtained in Example 8 is shown in Table 3, and the DSC chart is shown in Figure 14. From these results, it is speculated that the crystals obtained in Example 8 are a mixture (or mixed crystals) of α crystals and δ crystals.

[0080] [Table 3]

[0081] As is clear from Table 3, it was found that δ crystals can be obtained by crystallization using a crystallization solvent containing an aromatic hydrocarbon such as o-xylene and at least one component selected from 2-naphthol (phenols), MIBK (ketones), and 1,4-dioxane (ethers).

[0082] Furthermore, from Examples 2 and 3, it appears that the melting temperature does not have much effect on the formation of δ crystals. However, since α crystals were mixed in Example 8, which had a high precipitation temperature, it is believed that δ crystals are more easily formed when the precipitation temperature is low, as in Examples 1 to 7.

[0083] [Reference example 1] The δ crystal obtained in Example 1 was heated and melted in a heat block at 280° C., and then cooled to room temperature to obtain an amorphous body of BNF. When the obtained amorphous body was analyzed by XRD, a halo pattern was confirmed as shown in FIG. [Industrial Applicability]

[0084] The polymorph δ of BNF of the present invention has an extremely high melting point, and therefore has excellent thermal stability (or heat resistance) or storage stability in a high-temperature environment. In addition, since it has a 9,9-bisarylfluorene skeleton, it has various excellent properties, such as optical properties, heat resistance, water resistance, moisture resistance, chemical resistance, electrical properties, mechanical properties, and dimensional stability. Therefore, it can be suitably used as a raw material for industrial products, organic synthesis, and resin synthesis, and can also be suitably used as an additive (or resin additive) such as a heat resistance improver, a refractive index improver, and a curing agent for epoxy resins.

[0085] In addition, when used as a resin raw material, it is possible to efficiently impart excellent properties such as high heat resistance, high crosslinking, high refractive index, high transparency, and low linear expansion coefficient to the resin. Examples of such resins include thermosetting resins such as epoxy resins and (meth)acrylic resins (or polyfunctional (meth)acrylates), and thermoplastic resins such as polyester resins, polycarbonate resins, and polyurethane resins. The epoxy resins are suitable for applications requiring the above-mentioned properties, such as semiconductor sealants and electrical substrates. The (meth)acrylic resins are also useful for optical material applications, such as optical overcoats, hard coats, anti-reflection films, eyeglass lenses, optical fibers, optical waveguides, and holograms. The thermoplastic resins can also be used as molding materials for optical members, heat-resistant members, and the like.

Claims

1. A crystalline polymorph of 9,9-bis(6-hydroxy-2-naphthyl)fluorene, which has diffraction peaks at diffraction angles 2θ=9.6±0.2°, 14.2±0.2°, 17.5±0.2°, 20.6±0.2° and 21.3±0.2° in a powder X-ray diffraction pattern.

2. The crystalline polymorph δ according to claim 1, further having a diffraction peak at at least one angle selected from the diffraction angles 2θ=9.2±0.2°, 9.8±0.2°, 17.1±0.2°, 23.3±0.2° and 23.8±0.2°.

3. The crystalline polymorph δ according to claim 1 or 2, further having a diffraction peak at at least one angle selected from the diffraction angles 2θ=13.3±0.2°, 14.5±0.2°, 15.5±0.2° and 26.8±0.2°.

4. The crystalline polymorph δ according to any one of claims 1 to 3, having a melting point of 264±3°C.

5. A method for producing the crystalline polymorph δ according to any one of claims 1 to 4 by crystallizing 9,9-bis(6-hydroxy-2-naphthyl)fluorene from a mixed solvent of aromatic hydrocarbons and at least one solvent selected from phenols, ketones and ethers, wherein the ketones are C 3-8 ketone, and the ether is C 3-6 The method is a cyclic ether, and is precipitated at 80° C. or less.

6. 6. The method according to claim 5, wherein the ratio of the aromatic hydrocarbons to the total amount of the phenols, ketones and ethers (mass ratio) is from 70 / 30 to 90 / 10.

7. The method according to claim 5 or 6, wherein the precipitation is carried out at a temperature of from -10°C to 10°C.

Citation Information

Patent Citations

  • Solvate crystal of 9,9-bis(6-hydroxy naphthalene-2-group) fluorene and preparation thereof

    CN104230671A

  • Preparation of 9,9-bis(6-hydroxynaphthalene-2-yl) fluorene crystal without complex residual solvent

    CN108586205A

  • Compound having fluorene skeleton and method for producing the same

    JP2007099741A

  • Crystalline polymorph of 6,6-(9-fluorenylidene)-di(2-naphthol) and method for producing the same

    JP2012207008A

  • Manufacturing method of polycarbonate resin and polyester resin, polycarbonate resin and polyester resin

    JP2017171827A